A Study on Students' Writing Anxiety of English Study Program at FKIP UNRI - Ekasari, Salma Ardhanty; Novitri; Mahdum (PROJECT (Professional Journal of English Education), 2025)
The purpose of this research was to examine the levels, types, and causes of writing anxiety among third-year students in the English Study Program at FKIP Universitas Riau. A descriptive quantitative approach was employed in this study, utilizing a sample of 72 sixth-semester students chosen through cluster random sampling.. The data were gathered through a questionnaire adapted from Cheng's Second Language Writing Anxiety Inventory (SLWAI) (2004) and the Causes of Writing Anxiety Inventory (CWAI) created by Rezaei and Jafari (2014). The findings reveal that 37.5% of the students experienced high writing anxiety, 36.1% experienced moderate anxiety, and 26.4% experienced low anxiety. In terms of anxiety type, cognitive anxiety was the most dominant, followed by avoidance behavior and somatic anxiety. Additionally, the research identified linguistic difficulties as the primary cause of writing anxiety, accounting for 16.42%. This suggests that limited vocabulary, sentence structure issues, and grammar mastery are significant barriers for EFL students in academic writing tasks.